Exploring hyperlink structure of electronic commerce websites: a Webometric study. (22nd September 2010) - Rathimala, Kannan; Marthandan, Govindan
Hyperlink analysis, an emerging research area in web structure mining, extracts hidden information from hyperlink data. This study analyses the websites of USA's best 50 small companies to determine the association between the Webometrics data and business performance measures as well as traffic ranking. The results show that there is an association between the Webometrics data and the company's business information as well as traffic ranking. This suggests that Webometrics data could be used as an indicator for evaluating the business performance of the company as well as the visibility of its website to a target audience.